Advancing the Monitoring of Traditional Meadow Orchards: Current Approaches and Future Directions - P. Joseph; S. Pflüger; M. Petersen; A. Siegmund; A. Siegmund (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Meadow orchards represent critical components of European cultural landscapes and biodiversity, yet face significant threats from land-use intensification and management abandonment. Current studies show that the number of meadow orchards in Baden-Württemberg; Germany has declined sharply in recent decades and that existing trees are inadequately maintained. In this context, the aim of this study is to present an integrated remote sensing approach to monitor the ecological condition and management intensity of these cultural landscapes. Using high-resolution unmanned aerial system (UAS) imagery, we identified and assessed around 5,000 fruit trees in our study area near Bad Schönborn, Germany. Metrics such as canopy structure and spectral information such as NDVI were extracted, indicating high vitality (99%) but low maintenance (only 28% well maintained). Tree species classification accuracies ranged from 56% to 85%. The approach also emphasises stakeholder engagement and capacity building, embedding digital geo-information tools in community-based conservation. By combining UAS data with satellite imagery, the workflow is likely to be scalable across Baden-Württemberg to enable cost-effective, large-scale monitoring. Our findings highlight the role of advanced geospatial methods in meadow orchard conservation, bridging ecological knowledge with actionable landscape management.